Efektivitas platform guru virtual sebagai platform pembelajaran daring di masa pandemi covid-19 - Dewi Ratnaningsih (Aksara: Jurnal Bahasa dan Sastra, 2021)
Coronavirus or Covid-19 is viruses group of the Orthocoronavirinae member of Coronaviridae family and the order Nidovirales. This virus can cause disease not only human, but also birds and mammals. The extraordinary events caused by the corona virus become a new problem in various fields of life, including in the field of education. Every educator is required to be able to innovate, so that the learning process and physical limitations can both continue. Therefore, not long after the physical restriction instructions were applied, the online learning model or commonly referred to as e-learning began to be socialized. The purpose of writing this article is to see the effectiveness of the Guru Virtual platform as an daring learning medium. To conduct this research, researcher uses descriptive qualitative method. Qualitative descriptive method is a method that analyzes research in the form of descriptions not in the form of numbers or coefficients about the relationship between variables. The data gathered from the research is in the form of words or pictures not numbers. The data was collected by designing learning scenarios, recording, and interviewing. In addition, the calculation of student learning outcomes is also carried out to see learning outcomes using the Guru Virtual. Based on the results of interviews with students, Guru Virtual is an effective platform to be used as an daring learning platform. Based on the calculation of student learning outcomes, it was obtained an average value of 74.9 with a good category.